Relevance of Ijtihad Ibn Taimiyah to Contemporary Jurisprudence - Achmad Fageh (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
The ijtihad Ibn Taimiyyah update was built in two models of ijtihad; istidlal and istinbat. Relevance strengthening of the naqly istinbat evidence and the approach of rationality independence (istidlal) is urgently needed. Although in reality, Ibn Taimiyyah was more likely to wear the istinbat model than istidlal. Ibn Taimiyyah said the foundation of the ijtihad method comprehensively, the naqly and ‘aqly evidence applied simultaneously in every determination of Islamic law. Upon consideration of every sharia law, there must be a good content of shari'a purposes, then ibn Taimiyyah's most popular view is that valid shariah evidence must correlate with the correct rational evidence. Ibn Taymiyah's legal method uses: (1) the Qur'an, (2) sunnah, (3) ijmâ', (4) qiyas, (5) istishab, and (6) maslahah al-mursalah. There is a strong relevance between the renewal of ijtihad Ibn Taimiyyah and the development of Islamic law, especially in the field of contemporary jurisprudence with the approach of maslahah. Such as the ability to exchange and sell waqf property, the ability to appoint leaders from non-Muslims, the ability to buy and sell goods embedded in the ground, and the ability to buy and sell goods on credit. Abstrak: Pembaruan ijtihad Ibn Taimiyyah dibangun dalam dua model ijtihad; istidlal dan istinbat. Penguatan relevansi pembuktian naqly istinbat dan pendekatan independensi rasionalitas (istidlal) sangat dibutuhkan. Meski pada kenyataannya, Ibnu Taimiyyah lebih cenderung memakai model istinbat daripada istidlal. Ibnu Taimiyyah mengatakan landasan metode ijtihad secara komprehensif, dalil naqly dan 'aqlī diterapkan secara simultan dalam setiap penetapan hukum Islam. Berdasarkan pertimbangan setiap hukum syariah, harus ada isi yang baik dari tujuan syariah, maka pandangan paling populer ibn Taimiyyah adalah bahwa bukti syariah yang valid harus berkorelasi dengan bukti rasional yang benar. Metode hukum Ibnu Taimiyah menggunakan: (1) Al-Qur'an, (2) sunnah, (3) ijma', (4) qiyas, (5) istishab, dan (6) maslahah al-mursalah. Terdapat relevansi yang kuat antara pembaruan ijtihad Ibnu Taimiyyah dengan perkembangan hukum Islam, khususnya dalam bidang fikih kontemporer dengan pendekatan maṣlaḥaḥ. Seperti kemampuan menukar dan menjual harta wakaf, kemampuan mengangkat pemimpin dari non muslim, kemampuan jual beli barang yang disematkan di tanah, dan kemampuan jual beli barang secara kredit.